SIPOC METHOD OF OPTIMIZING THE CLINICAL PROCESS IN OBSTETRICS - Medjedovic, Edin; Spalldi Barisic, Lara; Nevacinovic, Enida; Rama, Admir; Kurtovic, Anida; Cerovac, Anis (Srpski medicinski časopis Lekarske komore, 2022)
The promptness of providing services to patients directly affects the success of healthcare organizations. In this regard, the implementation of contemporary concepts in healthcare organizations is synonymous with success.The subject being researched in this paper is the possibility of applying the SIPOC method to the clinical process in obstetrics. A more precise application of the abovementioned method would mean a prompter implementation of activities within the clinical process (pregestational counseling, antenatal care of expectant mothers, deliveries, supervision of women during puerperium). Through the activities of the abovementioned clinical process, an effort is made to meet the health needs of expectant and new mothers. The application of the SIPOC method is not sufficiently present in clinical processes, especially the clinical process in obstetrics, and therefore this paper opens a new research area.  The aim of this paper is to indicate the relevance of the SIPOC method as one of the tools within the Lean methodology, which can be used to improve the clinical process in obstetrics.The following materials and methods were applied in this study: the method of analysis, the inductive – deductive method, the method of synthesis, the method of description, the method of proof. Case analysis was also used in the application of the SIPOC matrix at a gynecology and obstetrics outpatient clinic.The results of the research showed that there was a positive impact on improving the efficiency of the provision of health services, through the implementation of modern methods. The SIPOC method affected the improvement of the efficiency of the clinical process in obstetrics. The review of the literature and the obtained results revealed that there is no formalized concept with instructions on the implementation of clinical process improvement methods.
Keywords: methods; health services; obstetrics